2020
DOI: 10.1192/j.eurpsy.2020.77
|View full text |Cite
|
Sign up to set email alerts
|

Baseline measures of cerebral glutamate and GABA levels in individuals at ultrahigh risk for psychosis: Implications for clinical outcome after 12 months

Abstract: Background. Cerebral glutamate and gamma-aminobutyric acid (GABA) levels might predict clinical outcome in individuals at ultrahigh risk (UHR) for psychosis but have previously primarily been investigated in smaller cohorts. We aimed to study whether baseline levels of glutamate and GABA in anterior cingulate cortex (ACC) and glutamate in thalamus could predict remission status and whether baseline metabolites differed in the remission versus the nonremission group. We also investigated the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Furthermore, reductions in LAUD cortex Glx concentration in CHR-P individuals did not predict APS persistence or functional outcomes, in line with a recent study ( 56 ). Previous findings, however, reported that glutamate levels in CHR-Ps predicted the severity of positive symptoms at follow up, in particular abnormal thought content ( 57 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, reductions in LAUD cortex Glx concentration in CHR-P individuals did not predict APS persistence or functional outcomes, in line with a recent study ( 56 ). Previous findings, however, reported that glutamate levels in CHR-Ps predicted the severity of positive symptoms at follow up, in particular abnormal thought content ( 57 ).…”
Section: Discussionsupporting
confidence: 90%
“…Further, another downstream metabolite of arginine is GABA. Tissue GABA levels were found to be reduced in brains of schizophrenia patients (39) pointing to aberrant glutamate release in target regions as its possible role in the pathophysiology of schizophrenia (41).…”
Section: Updating Biomarkers Research On Schizophreniamentioning
confidence: 99%
“…The PRISMA flow diagram is presented in Figure 1. Of the 54 studies, 23 studies included participants with psychosis (13– 15,17,36–53) (752 cases, 856 controls), 7 studies included individuals at UHR (47,53–58) (229 cases, 232 controls), 20 studies included individuals with depression (59–76) (463 cases, 499 controls), and 6 studies included participants with bipolar disorder (7782) (129 cases, 94 controls). Two studies included multiple clinical samples (47,53), therefore these numbers sum 56.…”
Section: Resultsmentioning
confidence: 99%